Characterisation of physical-chemical and fertility dynamics of mangrove soils from Guinea-Bissau in different agroecological conditions underlying paddy rice cultivation - Merkohasanaj,Matilda (2022)
Abstract Mangrove swamp rice production is of vital importance in most West African countries including Guinea Bissau. Even in a small country, different agroecological conditions underlying rice cultivation exist, and are mostly attributed to precipitation and temperature which impact soil acidity, salinity, and nutrient availability. The purpose of this study was to understand the physical, chemical, and nutritional properties of mangrove soils considering their variability and distribution in order to highlight the most adequate management practices. Based on field monitoring and three soil sampling dates, before and during the rice production cycle, in two different coastal regions of Guinea Bissau (Oio and Tombali), the most representative soil agroecological conditions were characterised. In the Tidal Mangrove (TM) swamps, the results showed that salinity and acidity concentrations were reduced to non-toxic levels at the nursery or transplantation moments. However, results from field observation showed that in those TM fields with limited drainage, the saltwater intrusion may create an imminent threat, with higher salt concentration corresponding to an electrical conductivity of approximately 6 mS cm−1 risking total production losses. In the Associated Mangrove (AM) swamps, acid and salinity levels do not pose a problem, but very low macronutrient levels (up to 2 times lower than TM), limite productivity in these soil. Furthermore, results showed high variability in physical chemical properties in the soils from the main agroecological conditions indentified and a positive down-stream gradient in soil fertility.